Effect of pH on soil improvement using one-phase-low-pH MICP or EICP biocementation method - Lai, Han-Jiang (2023)
One-phase-low-pH MICP (Microbially Induced Carbonate Precipitation) or EICP (Enzyme Induced Carbonate Precipitation) is a new biocementation method for soil improvement. This method uses the low pH of bacterial or urease solution to provide a delay for the MICP or EICP process so that the treatment solution can be evenly distributed in soil during grouting. However, how are the delay duration and the effect of biocementation affected by the initial pH (pH0) of bacterial or urease solution has not been studied. In this paper, an experimental study using different pH0 of urease (or bacterial) solution for EICP (or MICP) biocementation is presented. The study shows that the lower the pH0, the longer the delay period. However, the EICP or MICP process becomes ineffective when the pH0 is equal to or lower than 4.5 or 4.0 for EICP and MICP, respectively. The pH0 also has a significant effect on the strength of treated sand by affecting the morphology and crystallinity of precipitated calcium carbonate crystals. The pH0 on the other hand, has little effect on the amount of calcium carbonate production and its distribution in soil as long as the delay duration is sufficient for the distribution of treatment solution in soil.